A case report of neurological complications owing to lately diagnosed hyperargininemia emphasizing the role of national neonatal screening policies in the kingdom of Bahrain. Issue 20 (May 2018) - Bakhiet, Moiz; AlAwadi, Aminah M. I.; AlHammadi, Maryam M.; Ali, Maryam F.; Butti, Noora
Abstract: Introduction: Arginine is an essential amino acid that plays an important role in various body functions including cell division, wound healing, removal of ammonia, immune function, and release of hormones. Hyperargininemia, an autosomal recessive genetic disorder, is considered one of the least common urea cycle disorders. It rarely presents in the neonatal period but rather appears in children at the age between 2 and 4 years. Case Presentation: Herein, we demonstrate a case of a 14-year-old female who presented to the neurology clinic with several neurological complications, which were found to be a consequence of high levels of arginine discovered after performing a metabolic screening test. The hyperargininemia was because of a point mutation of A1 gene on 6q23 resulting in deficiency in arginase enzyme. The complications of this lately diagnosed case of hyperargininemia would have been avoided if a newborn screen were done as a part of a national program. Conclusion: This study presented certain neurological complications in a 14-year-old female who was lately diagnosed with hyperargininemia. Out case report strongly emphasizes the importance of establishing a national neonatal screening policy to ensure early detection of inherited metabolic disorders, in particular those which can be easily treated, in the Kingdom of Bahrain.